(untitled) (Economics and region, 2024)
The work established that the research of consumer loyalty of pharmaceutical products today is necessary not only for business, but also for society as a whole, since the interaction between pharmaceutical companies and consumers is determined not only by economic, but also by social aspects. Consumers of certain goods and services, in particular customers of pharmacy enterprises, have become less active, and more picky when making their purchases. In this connection, the competition in the market of pharmaceutical goods and services is increasing. Pharmacy chains have to spend more and more energy and financial resources in the competition for the loyalty of buyers of their products. This requires pharmaceutical companies to understand the specifics of the behavior of consumers of their products, in particular, to understand how certain individuals are committed to this product and to its distribution network. In this regard, it is relevant to study the loyalty of consumers of pharmaceutical products to a certain network of pharmacies. The purpose of the article is to analyze the current state of loyalty of consumers of pharmaceutical products and services based on a sociological survey of customers of a chain of pharmacy enterprises, as well as to study the factors affecting the loyalty of these customers. During the scientific research, the methods of questionnaire survey, inductive analysis, generalization and systematic approach were used. On the basis of a comparative analysis of the results of a survey of customers of a certain chain of pharmacies in Lviv regarding the quality of services of this chain, the diversity of its assortment, the level of prices, the convenience of the work schedule, the offer of promotional products and other factors, it was concluded that the attitude of this chain of its customers is quite good. It was found that almost 60% of the respondents pointed to the better quality of this chain compared to others, more than 87% of respondents would rather recommend this chain to friends and relatives, almost 80% of the customers of this chain rated the variety of its assortment as good or excellent. Moderate prices, convenient working hours, many promotional products and other positive aspects of the work of this chain of pharmacies attract customers to it. Some negative aspects of the activity of the researched pharmacy network were also revealed, which must be taken into account by its management in order to retain existing and attract new customers.